SCANNING RITEL STORE USING THE BUSINESS MODEL CANVAS METHOD - Ferry Hariawan; Nashrudin Latif (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The retail industry in Indonesia is currently experiencing unpredictable ups and downs. Many retail stores are closed and new ones keep popping up. Changes in the environment that keep happening make retail owners / management have to understand the changes themselves. For this reason, the business model must be determined in order to be able to compete with competitors. The purpose of this study is to determine the Wendys retail store business model using the (BMC) Business Model Canvas method. This research method uses descriptive analysis with the Business Model Canvas method using primary and secondary data. The customer segment of the Wendys retail store is local residents. Its value proposition is convenience of the shop building, product layout on the storefront, easy access, friendly service and product completeness. The main channels used are shop buildings and social media. Customer Relations is a delivery service for certain customers. Key activities are finding suppliers at low prices, purchasing products, processing products for sale (sorting, packaging), and keeping merchandise clean, well-maintained and resaleable. Main Resources owned are shop buildings, shop facilities and shop attendants. Its main partners are consumer goods suppliers and retail store communities. The cost structure includes operational costs which include product maintenance and maintenance, salaries, electricity, water. Non-operational costs depreciation of building value. The revenue stream is only from product sales.